Prospect Mapping Of Reservoir Z, Maari-Manaia Field, Taranaki Basin, New Zealand - Omar, Mohammad Ali Syafiq (2016)
This project is conducted to identify and map prospect Z of the Maari-Manaia field that can be encountered in the Moki Formation reservoir, which is a turbidite sand sediment. Seismic interpretation was conducted on the Maari 3D SEG-Y data, using the Maari-1 and Maari-2 well data as reference. The well data were used to identify the Moki formation top at the well location and the sand units in the formation. Seismic-to-well tie were conducted to identify seismic reflection which corresponds to the Moki formation top. The Moki formation top was then mapped from the 3D seismic volume using Petrel E&P software. Volumetric calculation was done using probabilistic method to estimate the volume of the oil reserve in the prospect.